A phase change sensor with energy storage and motion monitoring function, and a preparation method and application thereof

CN121761743BActive Publication Date: 2026-10-16CHINA UNIV OF MINING & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202512010380.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-29
Publication Date
2026-10-16
Estimated Expiration
2045-12-29

AI Technical Summary

Technical Problem

以解决现有传感器难以同时实现高效热能管理与精准运动监测,且柔韧性、稳定性和响应灵敏度有待提升的问题

Benefits of technology

本发明提供的相变传感器,包括从下往上依次设置的基底层、相变层和传感层,相变层是以粘合剂、相变材料和光电填料的复合物,相变层以粘合剂、相变材料和光电填料的复合物形成,利用石墨烯/碳纳米管的复配填料,保证吸光能力的同时构建导电网络,使得到的相变层兼具光/电热转化能力,可实现多能转化与储存;传感层是以热固性橡胶弹性基体和导电填料的复合物;以热固性橡胶弹性基体和导电填料的复合物,利用热固性橡胶弹性基体和粘合剂之间的相容性,以使相变层和传感层形成牢固不分层,且热固性橡胶弹性基体具有优异的机械性能,可弯曲180°以上仍然保持形状不断裂,并利用导电填料形成高效电子传输通道,增加响应灵敏度。集成了热管理层和传感层,兼顾高效热能储存与转化、精准运动监测,且具备良好柔韧性、稳定性和易制备性的相变传感器,具备优异的热能储存与转化能力,相变焓值大于140J/g,光热转换效率和电热转换效率分别可达85%和75%以上,能有效实现对环境温度或人体温度的调节,保障传感器在不同温度环境下的稳定工作;传感层响应灵敏度高,在180°形变时响应时间小于100ms,恢复时间小于120ms;且稳定性好,经过1000次循环形变后,相变焓值衰减小于3%,电流变化衰减率小于10%,可精准捕捉人体运动信号,实现高效的运动监测,适应不同的应用场景,提升了佩戴的舒适性和使用的便利性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121761743B_ABST
    Figure CN121761743B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electronic materials, and particularly relates to a phase change sensor with energy storage and motion monitoring functions, a preparation method and application. The phase change sensor comprises, from bottom to top, a substrate layer, a phase change layer and a sensing layer. The phase change layer is a composite of an adhesive, a phase change material and a photoelectric filler. The photoelectric filler is a composite of graphene and carbon nanotubes, and the mass ratio of graphene to carbon nanotubes is 0.25-1:1. The sensing layer is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer is arranged on the sensing layer, and the surfaces of the sensing layer and the electrode layer are covered with an encapsulation layer. The phase change sensor provided by the application has the functions of efficient heat energy storage and conversion, precise motion monitoring, good flexibility, stability and easy preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electronic materials technology, specifically relating to a phase change sensor that combines energy storage and motion monitoring, its preparation method, and its application. Background Technology

[0002] With the rapid development of wearable devices, smart healthcare, and human-computer interaction, higher demands are being placed on the multifunctional integration of sensors. Among them, sensors that simultaneously possess thermal management and motion monitoring functions have become a current research hotspot due to their enormous application potential in personal health monitoring, smart clothing, and industrial inspection.

[0003] Phase change materials (PCMs) possess the property of absorbing or releasing a large amount of latent heat during phase transitions, enabling the storage and release of thermal energy, and are widely used in the field of thermal energy management. Motion monitoring, however, requires sensors with excellent deformation sensing capabilities to convert mechanical deformation into detectable electrical signals. While existing PCM-based sensors can achieve thermal energy management, their sensing performance is poor, failing to accurately capture motion signals. Traditional motion sensors, on the other hand, lack effective thermal energy management capabilities. Under prolonged operation or in complex environments, temperature changes easily affect their stability and lifespan, resulting in insufficient flexibility and low response sensitivity. This makes it difficult to simultaneously achieve efficient thermal energy storage and conversion as well as accurate motion monitoring, limiting their practical application in wearable devices and other fields. Summary of the Invention

[0004] The purpose of this invention is to provide a phase change sensor that combines energy storage and motion monitoring, along with its fabrication method and applications. This addresses the limitations of existing sensors in simultaneously achieving efficient thermal management and accurate motion monitoring, and also highlights the need for improvements in flexibility, stability, and response sensitivity.

[0005] The present invention solves the above-mentioned technical problems through the following technical solutions.

[0006] The first objective of this invention is to provide a phase change sensor that combines energy storage and motion monitoring. The phase change sensor includes a substrate layer, a phase change layer, and a sensing layer arranged sequentially from bottom to top. The phase change layer is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a composite of graphene and carbon nanotubes, and the mass ratio of graphene to carbon nanotubes is 0.25 to 1:1. The sensing layer is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer is provided on the sensing layer, and both the sensing layer and the electrode layer are covered with an encapsulation layer.

[0007] Furthermore, the adhesive is polyvinylidene fluoride or polystyrene, and the phase change material is at least one of alkanes, fatty acids, and fatty alcohols. By mass percentage, in the phase change layer, the adhesive is 10% to 20%, the photoelectric filler is 10% to 20%, and the phase change material is 60% to 80%, totaling 100%.

[0008] Furthermore, the thermosetting rubber elastic matrix is ​​silicone rubber or nitrile rubber, and the conductive filler is a composite of carbon black and silver nanowires, with a mass ratio of carbon black to silver nanowires of 0.25 to 1:1.

[0009] Furthermore, the base layer is a polyimide film with a thickness of 50µm to 100µm.

[0010] The second objective of this invention is to provide a method for fabricating the aforementioned phase change sensor that combines energy storage and motion monitoring, comprising the following steps: S1. Phase change material and photoelectric filler are added sequentially to the adhesive solution, mixed to form a phase change layer slurry, and then coated onto the surface of the substrate layer and cured to obtain the phase change layer.

[0011] S2. Dissolve the thermosetting rubber elastic matrix and conductive filler in a solvent, mix them to form a sensing layer slurry, then coat it onto the surface of the phase change layer and dry it to obtain the sensing layer.

[0012] S3. Using screen printing technology, silver paste electrodes are printed on both ends of the sensing layer to obtain the electrode layer.

[0013] S4. After uniformly mixing the polydimethylsiloxane prepolymer and curing agent, an encapsulation layer precursor is formed, which is then coated onto the sensing layer and electrode surface and cured to obtain the encapsulation layer; thus, a phase change sensor is obtained.

[0014] Furthermore, the phase change layer slurry coating has a thickness of 100µm to 200µm, a curing temperature of 80℃ to 100℃, and a curing time of 1h to 2h; the adhesive in the adhesive solution has a mass fraction of 5% to 50%, and the solvent used in the adhesive solution is at least one of tetrahydrofuran, dimethylformamide, and dimethylacetamide.

[0015] Furthermore, in the sensing layer slurry, the mass fraction of conductive filler is 10% to 30%, the mass fraction of thermosetting rubber elastic matrix is ​​40% to 60%, and the thickness of the sensing layer slurry coating is 50µm to 100µm.

[0016] Furthermore, the thickness of the electrode layer is 10µm to 20µm.

[0017] Furthermore, the mass ratio of polydimethylsiloxane prepolymer to curing agent is 10:1, the thickness of the encapsulation layer precursor coating is 50µm to 100µm, the curing temperature is 80℃ to 100℃, and the curing time is 1h to 2h.

[0018] A third objective of this invention is to provide the application of the aforementioned phase change sensor, which combines energy storage and motion monitoring, in wearable thermal management devices, health monitoring devices, or smart industrial devices.

[0019] Compared with the prior art, the present invention has the following advantages: The phase change sensor provided by this invention includes a substrate layer, a phase change layer, and a sensing layer arranged sequentially from bottom to top. The phase change layer is a composite of an adhesive, a phase change material, and a photoelectric filler. Utilizing a graphene / carbon nanotube composite filler, it ensures light absorption while constructing a conductive network, giving the resulting phase change layer both photoelectric and electrothermal conversion capabilities, enabling multi-energy conversion and storage. The sensing layer is a composite of a thermosetting rubber elastic matrix and a conductive filler. By utilizing the compatibility between the thermosetting rubber elastic matrix and the adhesive, the phase change layer and sensing layer form a strong, non-delaminating structure. Furthermore, the thermosetting rubber elastic matrix possesses excellent mechanical properties, maintaining its shape even when bent more than 180° without breaking. The conductive filler forms a highly efficient electron transmission channel, increasing response sensitivity. This phase change sensor integrates a thermal management layer and a sensing layer, achieving both efficient thermal energy storage and conversion, and precise motion monitoring. It also boasts excellent flexibility, stability, and ease of fabrication. It exhibits superior thermal energy storage and conversion capabilities, with a phase change enthalpy greater than 140 J / g. Its photothermal conversion efficiency and electrothermal conversion efficiency reach over 85% and 75%, respectively, effectively regulating ambient or human body temperature to ensure stable operation under varying temperature conditions. The sensing layer demonstrates high sensitivity, with a response time of less than 100 ms and a recovery time of less than 120 ms at 180° deformation. Furthermore, it exhibits good stability, with the phase change enthalpy decreasing by less than 3% and the current change attenuation rate decreasing by less than 10% after 1000 cycles of deformation. This allows for precise capture of human motion signals, enabling efficient motion monitoring and adapting to diverse application scenarios, while enhancing wearing comfort and ease of use. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the phase change sensor of the present invention.

[0021] Figure 2 A physical image of the phase change sensor prepared for an embodiment of the present invention, which can be bent more than 180° and still maintain its shape without breaking.

[0022] Figure 3 The differential scanning calorimetry curve is shown for the phase change sensor prepared in Example 1 of the present invention.

[0023] Figure 4 The image shows the photothermal conversion efficiency of the phase change sensor prepared in Example 1 of this invention.

[0024] Figure 5 The diagram shows the electrothermal conversion efficiency of the phase change sensor prepared in Example 1 of this invention.

[0025] Figure 6 The current change rate of the phase change sensor prepared in Embodiment 1 of the present invention under different bending angles.

[0026] Figure 7 The image shows the response time curve of the phase change sensor prepared in Example 1 of this invention.

[0027] Figure 8 This is a photograph of the phase change sensor prepared in Comparative Example 1 of the present invention, which broke after being bent at 90°.

[0028] Figure 9 This is a photograph of the phase change sensor prepared in Comparative Example 2 of the present invention, which broke after being bent at 120°.

[0029] Figure 10 This is a photograph of the phase change sensor prepared in Comparative Example 3 of the present invention, which broke after being bent at 150°. Detailed Implementation

[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.

[0032] The purpose of this invention is to develop a phase change sensor that combines efficient thermal energy storage and conversion with precise motion monitoring, and possesses good flexibility, stability, and ease of fabrication. This addresses the limitations of existing sensors in simultaneously achieving efficient thermal energy management and precise motion monitoring, and the need to improve their flexibility, stability, and response sensitivity. Specifically:

[0033] A phase change sensor that combines energy storage and motion monitoring, such as Figure 1As shown, the phase change sensor includes a base layer 1, a phase change layer 2, and a sensing layer 3 arranged sequentially from bottom to top. The phase change layer 2 is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a composite of graphene and carbon nanotubes, and the mass ratio of graphene to carbon nanotubes is 0.25 to 1:1. The sensing layer 3 is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer 4 is provided on the sensing layer 3, and both the sensing layer 3 and the electrode layer 4 are covered with an encapsulation layer 5.

[0034] The phase change sensor provided by this invention has a phase change layer formed by a composite of a binder, a phase change material, and a photoelectric filler. Utilizing a graphene / carbon nanotube composite filler, it ensures light absorption while constructing a conductive network, giving the resulting phase change layer both photoelectric and electrothermal conversion capabilities, enabling multi-energy conversion and storage. More specifically, the photoelectric filler is a composite of graphene and carbon nanotubes at a mass ratio of 0.25 to 1:1. Utilizing the broad-spectrum absorption characteristics of the two-dimensional material graphene, combined with the one-dimensional light-trapping effect of carbon nanotubes, a highly efficient light-absorbing network can be constructed. Simultaneously, both are highly conductive materials, synergistically constructing a continuous conductive network, which exhibits Joule heating when energized. With significant effects and low energy loss, the highly efficient light-absorbing / conducting network constructed through this two-dimensional-one-dimensional multi-dimensional system ensures high-load phase change material while endowing it with photo / electrothermal conversion capabilities, enabling rapid absorption of light / electrical energy and conversion into thermal energy storage. The sensing layer is a composite of thermosetting rubber elastic matrix and conductive filler. Utilizing the compatibility between the thermosetting rubber elastic matrix and the adhesive, the phase change layer and sensing layer form a strong, non-delaminating structure. Furthermore, the thermosetting rubber elastic matrix possesses excellent mechanical properties, maintaining its shape even when bent more than 180° without breaking. The conductive filler forms a highly efficient electron transport channel, increasing response sensitivity. This invention integrates a thermal management layer and a sensing layer, achieving both efficient thermal energy storage and conversion, and precise motion monitoring. It also features a phase change sensor with excellent flexibility, stability, and ease of fabrication. The sensor possesses superior thermal energy storage and conversion capabilities, with a phase change enthalpy greater than 140 J / g. Its photothermal conversion efficiency and electrothermal conversion efficiency can reach over 85% and 75%, respectively, effectively regulating ambient or human body temperature and ensuring stable operation under different temperature conditions. The sensing layer exhibits high sensitivity, with a response time of less than 100 ms and a recovery time of less than 120 ms at 180° deformation. Furthermore, it demonstrates good stability, with the phase change enthalpy decreasing by less than 3% and the current change attenuation rate decreasing by less than 10% after 1000 cycles of deformation. This allows for precise capture of human motion signals and efficient motion monitoring.

[0035] In this invention, the two-dimensional planar structure of graphene and the one-dimensional material of carbon nanotubes are synergistically constructed to create a light-absorbing / conductive network, achieving photothermal and electrothermal conversion capabilities. However, when a single filler—graphene, carbon nanotubes, or other carbon materials—is present in a 10%–20% filler content, it cannot conduct electricity and therefore cannot achieve electrothermal conversion. When the mass ratio of graphene to carbon nanotubes exceeds 0.25–1:1, the enthalpy value drops significantly because the sheet-like graphene occupies a large amount of space; below this ratio, it is non-conductive and electrothermal conversion is impossible.

[0036] The phase change sensor provided by this invention has good flexibility and can be bent more than 180° while maintaining its shape without breaking; the sensor as a whole can be bent and folded, and can fit well with human skin or other flexible surfaces, adapting to different application scenarios and improving wearing comfort and ease of use.

[0037] In some embodiments, the adhesive is polyvinylidene fluoride or polystyrene, and the phase change material is at least one of alkanes, fatty acids, and fatty alcohols. By mass percentage, the phase change layer contains 10% to 20% adhesive, 10% to 20% photoelectric filler, and 60% to 80% phase change material, totaling 100%.

[0038] In some embodiments, the thermosetting rubber elastic matrix is ​​silicone rubber or nitrile rubber, and the conductive filler is a composite of carbon black and silver nanowires, with a mass ratio of carbon black to silver nanowires of 0.25 to 1:1. This invention utilizes a composite of silver nanowires and carbon black in the sensing layer. The silver nanowires provide efficient electron transport channels, while the carbon black fills the gaps between the nanowires, synergistically reducing material resistance, ensuring rapid signal transmission, and improving detection sensitivity. Carbon black enhances the dispersibility and mechanical stability of the silver nanowires, reducing aggregation and oxidation. Simultaneously, the material is easily compatible with flexible substrates and solution systems. Furthermore, carbon black is inexpensive, reducing the amount of silver nanowires required, thus lowering material costs while maintaining performance.

[0039] On the other hand, the present invention provides a method for fabricating the aforementioned phase change sensor that combines energy storage and motion monitoring, comprising the following steps: S1. Phase change material and photoelectric filler are added sequentially to the adhesive solution, mixed to form a phase change layer slurry, and then coated onto the surface of the substrate layer and cured to obtain the phase change layer.

[0040] In this invention, the substrate layer is a polyimide film with a thickness of 50µm to 100µm. Before use, impurities on the surface of the substrate layer need to be removed by ultrasonic cleaning with anhydrous ethanol for 10 to 20 minutes at a power of 100W. After ultrasonic cleaning, the substrate layer is dried at 60°C to 80°C for 1 to 2 hours to obtain the substrate layer.

[0041] In this invention, the adhesive is first dissolved in a solvent to form an adhesive solution. The adhesive solution contains 5% to 50% by mass of the adhesive, and the solvent used is at least one of tetrahydrofuran, dimethylformamide, and dimethylacetamide. In a preferred embodiment, the adhesive solution contains 10% to 30% by mass of the adhesive. Mixing is performed using ultrasonic mixing with a power of 200W to 400W for 10 to 30 minutes. In a preferred embodiment, the mass ratio of graphene to carbon nanotubes is 0.4 to 0.6:1. The phase change layer slurry is coated to a thickness of 100µm to 200µm, cured at 80℃ to 100℃ for 1 to 2 hours.

[0042] S2. Dissolve the thermosetting rubber elastic matrix and conductive filler in a solvent, mix them to form a sensing layer slurry, then coat it onto the surface of the phase change layer and dry it to obtain the sensing layer.

[0043] In this invention, the conductive filler comprises 10%–30% by mass in the sensing layer slurry, the thermosetting rubber elastic matrix comprises 40%–60% by mass, and the thickness of the sensing layer slurry coating is 50µm–100µm. The thermosetting rubber elastic matrix is ​​silicone rubber or nitrile rubber, the solvent is at least one of dimethylformamide, toluene, and ethyl acetate, and the conductive filler is a composite of carbon black and silver nanowires, with a carbon black to silver nanowire mass ratio of 0.25–1:1. In a preferred embodiment, the carbon black to silver nanowire mass ratio is 0.5–1:1. Mixing is performed using planetary stirring at a speed of 500 r / min–1500 r / min for 30 min–80 min. In a preferred embodiment, the stirring speed is 800 r / min–1000 r / min for 45 min–60 min. The drying temperature is 60℃~120℃ and the time is 2h~5h. In a preferred embodiment, the drying temperature is 80℃~100℃ and the time is 3h~4h.

[0044] S3. Using screen printing technology, silver paste electrodes are printed on both ends of the sensing layer to obtain the electrode layer.

[0045] In this invention, the thickness of the electrode layer is 10µm to 20µm. The width of the electrode is 2mm to 5mm, and the length is 5mm to 10mm.

[0046] S4. After uniformly mixing the polydimethylsiloxane prepolymer and curing agent, an encapsulation layer precursor is formed, which is then coated onto the sensing layer and electrode surface and cured to obtain the encapsulation layer; thus, a phase change sensor is obtained.

[0047] In this invention, the mass ratio of polydimethylsiloxane prepolymer to curing agent is 10:1, the thickness of the encapsulation layer precursor coating is 50µm to 100µm, the curing temperature is 80℃ to 100℃, and the curing time is 1h to 2h.

[0048] The phase change sensor fabrication method of this invention is simple and convenient to operate. Each step adopts conventional experimental equipment and processes, such as heating and stirring, ultrasonic dispersion, scraping coating, and screen printing. It does not require complex special equipment, which helps to reduce production costs, improve production efficiency, and facilitate large-scale mass production. The phase change sensor has good compatibility between its layers, avoiding delamination damage caused by performance differences between layers, and can achieve long-term stable use.

[0049] The phase change sensor with both energy storage and motion monitoring provided by this invention has significant practical implications and market value in applications such as wearable thermal management devices, health monitoring devices, and smart industrial equipment.

[0050] The following specific examples will provide further explanation.

[0051] Example 1 A phase change sensor that combines energy storage and motion monitoring, such as Figure 1 As shown, the phase change sensor includes a base layer 1, a phase change layer 2, and a sensing layer 3 arranged sequentially from bottom to top. The phase change layer 2 is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a composite of graphene and carbon nanotubes, with a mass ratio of graphene to carbon nanotubes of 2:3. The sensing layer 3 is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer 4 is provided on the sensing layer 3, and both the sensing layer 3 and the electrode layer 4 are covered with an encapsulation layer 5.

[0052] The above-mentioned method for fabricating a phase change sensor that combines energy storage and motion monitoring includes the following steps: S1, Substrate layer: A 50µm thick polyimide film is ultrasonically cleaned with anhydrous ethanol at 100W for 20 minutes, and then dried at 80℃ for 1 hour to obtain the substrate layer.

[0053] S2, Phase Change Layer: Dissolve 5g of polyvinylidene fluoride in 45g of dimethylformamide, then add 15g of docosane and stir to dissolve. Next, add 2g of graphene and 3g of carbon nanotubes in sequence. Sonicate at 400W for 20min to mix evenly and obtain a phase change layer slurry. Coat the phase change layer slurry on the substrate with a thickness of 150µm and cure at 80℃ for 2h to obtain the phase change layer.

[0054] S3, Sensing Layer: Mix 5g of carbon black, 5g of silver nanowires, 40g of silicone rubber and 50g of dimethylformamide, add to a planetary mixer, mix at 1000r / min for 45min to obtain a sensing layer slurry, coat the sensing layer slurry on the phase change layer to a thickness of 50µm, and dry at 80℃ for 2h to obtain the sensing layer.

[0055] S4, Motor Layer: Using screen printing, silver paste electrodes are printed at both ends of the sensing layer. The electrodes are 4mm wide, 10mm long, and 10µm thick. They are then dried at 100℃ for 30 minutes to obtain the electrode layer.

[0056] S5. Encapsulation Layer: Mix 5g of polydimethylsiloxane prepolymer and 0.5g of curing agent evenly to form the encapsulation layer precursor. Then, coat the precursor with a thickness of 100µm on the surface of the sensing layer and electrode, and cure at 100℃ for 1h to obtain the encapsulation layer. This yields the phase change sensor.

[0057] The phase change sensor prepared in Example 1 of this invention has good flexibility, such as... Figure 2 As shown, it can be bent more than 180° and still maintain its shape without breaking. Figure 3 This is a differential scanning calorimetry curve of the phase change sensor prepared in Example 1 of the present invention. Figure 3 As shown, the phase change enthalpy of the phase change sensor prepared in Example 1 is approximately 160 J / g. Figure 4 This is a graph showing the photothermal conversion efficiency of the phase change sensor prepared in Example 1 of the present invention. Figure 4 As shown, at 100mW / cm 2 Under the given light intensity, the photothermal conversion efficiency is 95%. Figure 5 This is a graph showing the electrothermal conversion efficiency of the phase change sensor prepared in Example 1 of the present invention. Figure 5 As shown, the electrothermal conversion efficiency is 80% at a current of 0.1A. Figure 6 The current change rate of the phase change sensor prepared in Embodiment 1 of the present invention under different bending angles. Figure 6 As shown, different current signals can be generated for different degrees of bending. When the deformation is about 180°, the current change rate is about 2.5. Figure 7 This is a response time curve of the phase change sensor prepared in Example 1 of the present invention. Figure 7 As shown, the response time is approximately 80 ms and the recovery time is approximately 100 ms. After the phase change sensor prepared in Example 1 undergoes 1000 bending deformation cycles, the phase change enthalpy decreases by 1% and the current change rate decreases by 5%.

[0058] Example 2 A phase change sensor that combines energy storage and motion monitoring, such as Figure 1As shown, the phase change sensor includes a base layer 1, a phase change layer 2, and a sensing layer 3 arranged sequentially from bottom to top. The phase change layer 2 is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a composite of graphene and carbon nanotubes, with a mass ratio of graphene to carbon nanotubes of 1:1. The sensing layer 3 is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer 4 is provided on the sensing layer 3, and both the sensing layer 3 and the electrode layer 4 are covered with an encapsulation layer 5.

[0059] The above-mentioned method for fabricating a phase change sensor that combines energy storage and motion monitoring includes the following steps: S1, Substrate layer: A 50µm thick polyimide film is ultrasonically cleaned with anhydrous ethanol at 100W for 20 minutes, and then dried at 80℃ for 1 hour to obtain the substrate layer.

[0060] S2, Phase Change Layer: Dissolve 5g of polyvinylidene fluoride in 45g of dimethylformamide, then add 15g of docosane and stir to dissolve. Next, add 2g of graphene and 3g of carbon nanotubes in sequence. Sonicate at 400W for 20min to mix evenly and obtain a phase change layer slurry. Coat the phase change layer slurry on the substrate with a thickness of 150µm and cure at 80℃ for 2h to obtain the phase change layer.

[0061] S3, Sensing Layer: Mix 5g of carbon black, 5g of silver nanowires, 40g of silicone rubber and 50g of dimethylformamide, add to a planetary mixer, mix at 1000r / min for 45min to obtain a sensing layer slurry, coat the sensing layer slurry on the phase change layer to a thickness of 50µm, and dry at 80℃ for 2h to obtain the sensing layer.

[0062] S4, Motor Layer: Using screen printing, silver paste electrodes are printed at both ends of the sensing layer. The electrodes are 4mm wide, 10mm long, and 10µm thick. They are then dried at 100℃ for 30 minutes to obtain the electrode layer.

[0063] S5. Encapsulation Layer: Mix 5g of polydimethylsiloxane prepolymer and 0.5g of curing agent evenly to form the encapsulation layer precursor. Then, coat the precursor with a thickness of 100µm on the surface of the sensing layer and electrode, and cure at 100℃ for 1h to obtain the encapsulation layer. This yields the phase change sensor.

[0064] The phase change sensor prepared in Example 2 of this invention exhibits good flexibility, maintaining its shape without breakage even after being bent more than 180°. The phase change enthalpy is approximately 180 J / g; the photothermal conversion efficiency is 85% (100 mW / cm²). 2Light intensity); electrothermal conversion efficiency of 85% (0.1A current); it can generate different current signals for different degrees of bending. When the deformation is about 180°, the current change rate is about 4, the response time is about 100ms, and the recovery time is about 120ms; after 1000 bending deformation cycles, the phase transition enthalpy decreases by 2% and the current change rate decreases by 8%.

[0065] Example 3 A phase change sensor that combines energy storage and motion monitoring, such as Figure 1 As shown, the phase change sensor includes a base layer 1, a phase change layer 2, and a sensing layer 3 arranged sequentially from bottom to top. The phase change layer 2 is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a composite of graphene and carbon nanotubes, with a mass ratio of graphene to carbon nanotubes of 1:1. The sensing layer 3 is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer 4 is provided on the sensing layer 3, and both the sensing layer 3 and the electrode layer 4 are covered with an encapsulation layer 5.

[0066] The above-mentioned method for fabricating a phase change sensor that combines energy storage and motion monitoring includes the following steps: S1, Substrate layer: A 50µm thick polyimide film is ultrasonically cleaned with anhydrous ethanol at 100W for 20 minutes, and then dried at 80℃ for 1 hour to obtain the substrate layer.

[0067] S2, Phase Change Layer: Dissolve 5g of polyvinylidene fluoride in 45g of dimethylformamide, then add 15g of docosane and stir to dissolve. Next, add 2g of graphene and 3g of carbon nanotubes in sequence. Sonicate at 400W for 20min to mix evenly and obtain a phase change layer slurry. Coat the phase change layer slurry on the substrate with a thickness of 150µm and cure at 80℃ for 2h to obtain the phase change layer.

[0068] S3, Sensing Layer: Mix 5g of carbon black, 5g of silver nanowires, 40g of silicone rubber and 50g of dimethylformamide, add to a planetary mixer, mix at 1000r / min for 45min to obtain a sensing layer slurry, coat the sensing layer slurry on the phase change layer to a thickness of 50µm, and dry at 80℃ for 2h to obtain the sensing layer.

[0069] S4, Motor Layer: Using screen printing, silver paste electrodes are printed at both ends of the sensing layer. The electrodes are 4mm wide, 10mm long, and 10µm thick. They are then dried at 100℃ for 30 minutes to obtain the electrode layer.

[0070] S5. Encapsulation Layer: Mix 5g of polydimethylsiloxane prepolymer and 0.5g of curing agent evenly to form the encapsulation layer precursor. Then, coat the precursor with a thickness of 100µm on the surface of the sensing layer and electrode, and cure at 100℃ for 1h to obtain the encapsulation layer. This yields the phase change sensor.

[0071] The phase change sensor prepared in Example 3 of this invention exhibits good flexibility, maintaining its shape without breakage even after bending more than 180°; the phase change enthalpy is approximately 145 J / g; and the photothermal conversion efficiency is 90% (100 mW / cm²). 2 Light intensity); electrothermal conversion efficiency of 88% (0.1A current); can generate different current signals for different degrees of bending. When the deformation is about 180°, the current change rate is about 3.5, the response time is about 90ms, and the recovery time is about 105ms; after 1000 bending deformation cycles, the phase transition enthalpy decreases by 1%, and the current change rate decreases by 3%.

[0072] Comparative Example 1 A phase change sensor, which differs from Embodiment 1 in that it has no photoelectric filler; the phase change sensor includes a base layer 1, a phase change layer 2 and a sensing layer 3 arranged sequentially from bottom to top. The phase change layer 2 is a composite of an adhesive and a phase change material; the sensing layer 3 is a composite of a thermosetting rubber elastic matrix and a conductive filler; an electrode layer 4 is provided on the sensing layer 3, and both the sensing layer 3 and the electrode layer 4 are covered with an encapsulation layer 5.

[0073] The above-mentioned method for fabricating a phase change sensor that combines energy storage and motion monitoring includes the following steps: S1, Substrate layer: A 50µm thick polyimide film is ultrasonically cleaned with anhydrous ethanol at 100W for 20 minutes, and then dried at 80℃ for 1 hour to obtain the substrate layer.

[0074] S2, Phase Change Layer: Dissolve 5g of polyvinylidene fluoride in 45g of dimethylformamide, then add 15g of docosane and stir. Sonicate at 400W for 20min to obtain a uniform phase change layer slurry. Apply the phase change layer slurry to the substrate with a thickness of 150µm and cure at 80℃ for 2h to obtain the phase change layer.

[0075] S3, Sensing Layer: Mix 5g of carbon black, 5g of silver nanowires, 40g of silicone rubber and 50g of dimethylformamide, add to a planetary mixer, mix at 1000r / min for 45min to obtain a sensing layer slurry, coat the sensing layer slurry on the phase change layer to a thickness of 50µm, and dry at 80℃ for 2h to obtain the sensing layer.

[0076] S4, Motor Layer: Using screen printing, silver paste electrodes are printed at both ends of the sensing layer. The electrodes are 4mm wide, 10mm long, and 10µm thick. They are then dried at 100℃ for 30 minutes to obtain the electrode layer.

[0077] S5. Encapsulation Layer: Mix 5g of polydimethylsiloxane prepolymer and 0.5g of curing agent evenly to form the encapsulation layer precursor. Then, coat the precursor with a thickness of 100µm on the surface of the sensing layer and electrode, and cure at 100℃ for 1h to obtain the encapsulation layer. This yields the phase change sensor.

[0078] The phase change sensor prepared in Comparative Example 1 of this invention has poor flexibility, such as... Figure 8 As shown, it fractures after bending 90°; the phase transition enthalpy is about 200 J / g; it does not have photothermal / electrothermal conversion capabilities; it can generate different current signals for different degrees of bending, and the current change rate is about 1.0 when the deformation is about 90°; the response time is about 150 ms and the recovery time is about 160 ms.

[0079] Comparative Example 2 A phase change sensor, differing from Example 1 in that the photoelectric filler is only graphene; such as Figure 1 As shown, the phase change sensor includes a base layer 1, a phase change layer 2, and a sensing layer 3 arranged sequentially from bottom to top. The phase change layer 2 is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a single graphene. The sensing layer 3 is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer 4 is provided on the sensing layer 3, and both the sensing layer 3 and the electrode layer 4 are covered with an encapsulation layer 5.

[0080] The above-mentioned method for fabricating a phase change sensor that combines energy storage and motion monitoring includes the following steps: S1, Substrate layer: A 50µm thick polyimide film is ultrasonically cleaned with anhydrous ethanol at 100W for 20 minutes, and then dried at 80℃ for 1 hour to obtain the substrate layer.

[0081] S2, Phase Change Layer: Dissolve 5g of polyvinylidene fluoride in 45g of dimethylformamide, then add 15g of docosane and stir to dissolve. Then add 5g of graphene in sequence and sonicate at 400W for 20min to obtain a phase change layer slurry. Coat the phase change layer slurry on the substrate with a thickness of 150µm and cure at 80℃ for 2h to obtain the phase change layer.

[0082] S3, Sensing Layer: Mix 5g of carbon black, 5g of silver nanowires, 40g of silicone rubber and 50g of dimethylformamide, add to a planetary mixer, mix at 1000r / min for 45min to obtain a sensing layer slurry, coat the sensing layer slurry on the phase change layer to a thickness of 50µm, and dry at 80℃ for 2h to obtain the sensing layer.

[0083] S4, Motor Layer: Using screen printing, silver paste electrodes are printed at both ends of the sensing layer. The electrodes are 4mm wide, 10mm long, and 10µm thick. They are then dried at 100℃ for 30 minutes to obtain the electrode layer.

[0084] S5. Encapsulation Layer: Mix 5g of polydimethylsiloxane prepolymer and 0.5g of curing agent evenly to form the encapsulation layer precursor. Then, coat the precursor with a thickness of 100µm on the surface of the sensing layer and electrode, and cure at 100℃ for 1h to obtain the encapsulation layer. This yields the phase change sensor.

[0085] The phase change sensor prepared in Comparative Example 2 of this invention has poor flexibility, such as... Figure 9 As shown, fracture occurs after bending 120°; the phase transition enthalpy is approximately 140 J / g; and the photothermal conversion efficiency is 85% (100 mW / cm²). 2 (Light intensity); It does not have the ability to convert light into heat; It can generate different current signals for different degrees of bending. When the deformation is about 120°, the current change rate is about 1.2; The response time is about 120ms and the recovery time is about 100ms.

[0086] Comparative Example 3 A phase change sensor, differing from Example 1 in that the photoelectric filler is only carbon nanotubes; such as Figure 1 As shown, the phase change sensor includes a base layer 1, a phase change layer 2, and a sensing layer 3 arranged sequentially from bottom to top. The phase change layer 2 is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a single carbon nanotube. The sensing layer 3 is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer 4 is provided on the sensing layer 3, and both the sensing layer 3 and the electrode layer 4 are covered with an encapsulation layer 5.

[0087] The above-mentioned method for fabricating a phase change sensor that combines energy storage and motion monitoring includes the following steps: S1, Substrate layer: A 50µm thick polyimide film is ultrasonically cleaned with anhydrous ethanol at 100W for 20 minutes, and then dried at 80℃ for 1 hour to obtain the substrate layer.

[0088] S2, Phase Change Layer: Dissolve 5g of polyvinylidene fluoride in 45g of dimethylformamide, then add 15g of docosane and stir to dissolve. Next, add 5g of carbon nanotubes and sonicate at 400W for 20 minutes to obtain a phase change layer slurry. Coat the phase change layer slurry on the substrate with a thickness of 150µm and cure at 80℃ for 2 hours to obtain the phase change layer.

[0089] S3, Sensing Layer: Mix 5g of carbon black, 5g of silver nanowires, 40g of silicone rubber and 50g of dimethylformamide, add to a planetary mixer, mix at 1000r / min for 45min to obtain a sensing layer slurry, coat the sensing layer slurry on the phase change layer to a thickness of 50µm, and dry at 80℃ for 2h to obtain the sensing layer.

[0090] S4, Motor Layer: Using screen printing, silver paste electrodes are printed at both ends of the sensing layer. The electrodes are 4mm wide, 10mm long, and 10µm thick. They are then dried at 100℃ for 30 minutes to obtain the electrode layer.

[0091] S5. Encapsulation Layer: Mix 5g of polydimethylsiloxane prepolymer and 0.5g of curing agent evenly to form the encapsulation layer precursor. Then, coat the precursor with a thickness of 100µm on the surface of the sensing layer and electrode, and cure at 100℃ for 1h to obtain the encapsulation layer. This yields the phase change sensor.

[0092] The phase change sensor prepared in Comparative Example 3 of this invention has poor flexibility, such as... Figure 10 As shown, fracture occurs after bending 150°; the phase transition enthalpy is approximately 150 J / g; and the photothermal conversion efficiency is 80% (100 mW / cm²). 2 (Light intensity); It does not have electrothermal conversion capability; It can generate different current signals for different degrees of bending. When the deformation is about 150°, the current change rate is about 1.5; The response time is about 110ms and the recovery time is about 100ms.

[0093] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.

[0094] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A phase change sensor that combines energy storage and motion monitoring, characterized in that, The phase change sensor comprises a substrate layer, a phase change layer, and a sensing layer arranged sequentially from bottom to top. The phase change layer is a composite of an adhesive, a phase change material, and a photoelectric filler, wherein the photoelectric filler is a composite of graphene and carbon nanotubes, with a mass ratio of graphene to carbon nanotubes of 0.25 to 1:

1. The sensing layer is a composite of a thermosetting rubber elastic matrix and a conductive filler. An electrode layer is provided on the sensing layer, and both the sensing layer and the electrode layer are covered with an encapsulation layer. The base layer is a polyimide film; The binder is polyvinylidene fluoride or polystyrene, and the phase change material is at least one of alkanes, fatty acids, and fatty alcohols. By mass percentage, in the phase change layer, the binder is 10% to 20%, the photoelectric filler is 10% to 20%, and the phase change material is 60% to 80%, totaling 100%. The thermosetting rubber elastic matrix is ​​silicone rubber or nitrile rubber, and the conductive filler is a composite of carbon black and silver nanowires, with a mass ratio of carbon black to silver nanowires of 0.25 to 1:

1.

2. The phase change sensor combining energy storage and motion monitoring according to claim 1, characterized in that, The thickness of the substrate layer is 50µm to 100µm.

3. A method for fabricating a phase change sensor combining energy storage and motion monitoring as described in claim 1 or 2, characterized in that, Includes the following steps: A phase change material and a photoelectric filler are added sequentially to an adhesive solution, mixed to form a phase change layer slurry, and then coated onto the surface of a substrate layer and cured to obtain a phase change layer. Thermosetting rubber elastic matrix and conductive filler are dissolved in solvent and mixed to form a sensing layer slurry, which is then coated onto the surface of the phase change layer and dried to obtain the sensing layer. Silver paste electrodes are printed on both ends of the sensing layer using screen printing technology to obtain the electrode layer. The polydimethylsiloxane prepolymer and curing agent are mixed evenly to form an encapsulation layer precursor, which is then coated onto the sensing layer and electrode surface and cured to obtain the encapsulation layer. This yields a phase change sensor.

4. The method for fabricating a phase change sensor combining energy storage and motion monitoring according to claim 3, characterized in that, The phase change layer slurry has a coating thickness of 100µm to 200µm, a curing temperature of 80℃ to 100℃, and a curing time of 1h to 2h. The adhesive in the adhesive solution has a mass fraction of 5% to 50%, and the solvent used in the adhesive solution is at least one of tetrahydrofuran, dimethylformamide, and dimethylacetamide.

5. The method for fabricating a phase change sensor combining energy storage and motion monitoring according to claim 3, characterized in that, In the sensing layer slurry, the mass fraction of conductive filler is 10% to 30%, the mass fraction of thermosetting rubber elastic matrix is ​​40% to 60%, and the thickness of the sensing layer slurry coating is 50µm to 100µm.

6. The method for fabricating a phase change sensor combining energy storage and motion monitoring according to claim 3, characterized in that, The thickness of the electrode layer is 10µm to 20µm.

7. The method for fabricating a phase change sensor combining energy storage and motion monitoring according to claim 3, characterized in that, The mass ratio of polydimethylsiloxane prepolymer to curing agent is 10:1, the thickness of the encapsulation layer precursor coating is 50µm to 100µm, the curing temperature is 80℃ to 100℃, and the curing time is 1h to 2h.

8. The application of a phase change sensor with both energy storage and motion monitoring as described in claim 1 or 2 in wearable thermal management devices, health monitoring devices, or smart industrial devices.

Citation Information

Patent Citations

  • Flexible phase change energy storage sensor and preparation method and application thereof

    CN115045043A

  • Wearable photo-thermal phase change energy storage composite film and preparation method thereof

    CN116574298A